1978
DOI: 10.1037/0033-2909.85.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches to the etiology and treatment of anorexia nervosa.

Abstract: The first section of this paper reviews the literature on the incidence, clinical findings, and outcome of anorexia nervosa. Methodological problems with outcome statistics and data on the family background of anorexic patients are discussed. The remainder of this paper evaluates the etiological and therapeutic approaches of psychodynamic, family interactional, behavioral, and medical models. The problems inherent in viewing anorexia nervosa as either a physiological or psychological disorder are considered. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
2

Year Published

1983
1983
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(86 citation statements)
references
References 146 publications
(293 reference statements)
4
80
0
2
Order By: Relevance
“…1,2 In the United States, 90% of those who suffer from anorexia nervosa 3 and bulimia nervosa 4 are women. Research conducted in Israel shows results similar to those obtained in Western cultures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the United States, 90% of those who suffer from anorexia nervosa 3 and bulimia nervosa 4 are women. Research conducted in Israel shows results similar to those obtained in Western cultures.…”
Section: Introductionmentioning
confidence: 99%
“…No other consistent patterns of family characteristics were seen in these studies either (reported in Bemis, 1978). Perhaps Yager (1982) presents the most accurate profile of family characteristics, reporting that research has identified a range of mother-daughter relationships extending from the overprotective to ambivalent to rejecting to "normal.…”
Section: Family Influencementioning
confidence: 78%
“…In the recent literature, there are a variety of attempts to explain anorexia nervosa and bulimia, ranging from biological to family systems explanations (Bemis, 1978;Hsu, 1983). There is a growing consensus that familial, biological, and sociocultural factors all contribute to the development of both anorexia and bulimia (Johnson & Flach, 1985).…”
Section: Etiologymentioning
confidence: 99%
“…This is espe cially important in the case of anorexia ner vosa because therapeutic approaches are widely divergent (e.g., pharmacological, learning theory oriented, psychoanalytic, system oriented, multifactorial) [Vandereycken and Meermann, 1984], direct therapy comparisons have hardly been feasible until now, and the numerous studies on prognos tic factors only classified the latter as posi tive, negative, or irrelevant [e.g., Crisp et al, 1977;Bemis, 1978;Steinhausen, 1979;Fichter, 1981a;Kohle and Simons, 1986] without establishing an empirically founded hierarchical order based on the relative im portance of the areas under investigation. This study attempts to make up for that defi ciency.…”
Section: Introductionmentioning
confidence: 99%